Comprehensive Bioinformatics Analysis Identifies POLR2I as a Key Gene in the Pathogenesis of Hypertensive Nephropathy - You, Shilong; Xu, Jiaqi; Wu, Boquan; Wu, Shaojun; Zhang, Ying; Sun, Yingxian; Zhang, Naijin (Frontiers in Genetics, 2021)
Hypertensive nephropathy, mainly caused by chronic hypertension, is one of the major causes of end-stage renal disease. However, the pathogenesis of HN remains unclarified, and there is an urgent need for improved treatments. HN and control tubulointerstitial tissue samples from the GSE37455 and the GSE104954 were separately and randomly divided into two non-overlapping groups for subsequent cross validation. 385 overlapping differentially expressed genes (DEGs) were identified by weighted gene co-expression network analysis (WGCNA) and DEGs analysis. Enrichment analysis suggested that the overlapping DEGs were associated with various transcription related and redox related processes, which were potentially related to the development of HN. Protein-protein interaction network analysis revealed that POLR2G is one of the most central genes in the overlapping DEGs. Furthermore, we found abnormal up-regulation of POLR2G in HN, which is associated with impaired renal function in HN after independent validation and clinical validation. Finally, gene set variation analysis indicated that POLR2G may be involved in the regulation of HN by affecting metabolism-related activities. In conclusion, our study identified POLR2G as a key gene related to the pathogenesis of HN, which provides new insights into the molecular mechanisms underlying HN.